Geographical Information Systems (GIS) in Municipal Planning and Management: A Pathway to Improve South African Service Delivery - Racheku, Kamogelo; Kgobe, France Khutso Lavhelani (Journal of Governance Risk Management Compliance and Sustainability, 2024)
In the years after 1994, the democratic government of South Africa worked to transfer and extend basic service provision to practically all sections of the country. The delivery of public services continues to be an embarrassment to humanity and the developmental state. Without proper basic services such as water, sanitation, power, infrastructure, health facilities, and housing, a large section of South Africa’s people would continue to live and die. As a result, society remains disenfranchized and exposed to socioeconomic shocks, contributing to the economy's decline and destruction. To support successful service delivery, the integration of Geographical Information Systems (GIS) as a shift from human-led operations to computerized operations is now recognized and required in municipal planning and management. The central purpose of this study is to evaluate the feasibility of applying GIS as a crucial planning tool infused within integrated development planning in municipal planning and management. The current state of service delivery in existing municipal planning and management procedures, as well as the factors that influence it and the effect it has on society, will be examined. This conceptual study employs secondary data and follows a certain methodology. Using the Critical Discourse Analysis (CDA) methodology, secondary data were examined. The results demonstrate that political influence and manipulation, a lack of openness and accountability, insufficient citizen participation, a lack of personnel capability, and poor planning, monitoring, and evaluation contribute to poor public service delivery in South Africa. Furthermore, the findings indicate that GIS functions as a tool for visualization and collation of spatial information, map production, and data capturing and storage in local municipalities with the aim of enhancing public service delivery.